2011
DOI: 10.1007/s00107-011-0571-x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of water adsorption by wood using the Guggenheim-Anderson-de Boer equation

Abstract: The Guggenheim-Anderson-de Boer (GAB) three-parameter sorption equation has been used to interpret the adsorption and desorption isotherms of water vapour measured for 21 important cultural heritage wood species used in the past for panel paintings and woodcarving. The equation is capable of describing the full shape of the isotherms and yields meaningful physical parameters, especially the monolayer capacity from which the water accessible specific surface area can be obtained. It is demonstrated that average… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(55 citation statements)
references
References 10 publications
2
50
0
3
Order By: Relevance
“…The modified GAB model gave a better fit than the original model for the experimental data obtained from the moisture adsorption isotherms in the range from 0.10 to 0.90 a w (Table 3). As the parameters of the GAB equation are based on the physical phenomena involved in water adsorption by hydrophilic materials, it is considered the most suitable model to describe experimental data (Bratasz et al, 2012;Figura & Teixeira, 2007;Furmaniak et al, 2007;Lavoyer et al, 2013;Medeiros et al, 2006;Souza et al, 2015;Timmermann et al, 2001;Zhang & Han, 2008).…”
Section: Modeling Of Experimental Datamentioning
confidence: 99%
“…The modified GAB model gave a better fit than the original model for the experimental data obtained from the moisture adsorption isotherms in the range from 0.10 to 0.90 a w (Table 3). As the parameters of the GAB equation are based on the physical phenomena involved in water adsorption by hydrophilic materials, it is considered the most suitable model to describe experimental data (Bratasz et al, 2012;Figura & Teixeira, 2007;Furmaniak et al, 2007;Lavoyer et al, 2013;Medeiros et al, 2006;Souza et al, 2015;Timmermann et al, 2001;Zhang & Han, 2008).…”
Section: Modeling Of Experimental Datamentioning
confidence: 99%
“…The isotherms were modelled using the Guggenheim, Anderson and Boer-Dent (GAB) expression. This model is particularly appropriate for food materials and widely used for multi-layer materials such as wood (Bratasz et al 2011). GAB system general equation is reported in eqn.…”
Section: Moisture Relations Assessmentmentioning
confidence: 99%
“…Experimental studies using this type of isotherm can be found mainly on (multilayer-like) adsorption, e.g. water on synthetic and natural polymers, starch, wood or food [33][34][35][36][37]. To the best of our knowledge, there are only two studies applying a multilayer-like adsorption model like GAB or BET to the uptake of phosphoric acid and water in polybenzimidazole [24,38].…”
Section: Limiting Cases For Low and High Concentrations Of The Dopingmentioning
confidence: 97%